Impactos del turismo y de la conmutación centrípeta-centrífuga en el Sur de Chile: Enfoques clásicos y nuevos para su interpretación - Sergio Soza-Amigo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– Given the closeness of Valdivia, Osorno, Puerto Montt and Entre Lagos to Puyehue National Park (PNP), this article reviews the economic impact of the increased visits. We also study the salary changes required in order to motivate work in the area, using commutation as proxy of the labour market. As a novelty, the so-called "commuter-word-of-mouth" effect is to be highlighted,as well as the use of a formulation that explains how income affects commutation. This research provides answers to the following questions: Is the contribution of tourism relevant to these villages? Is there some correlation between an allometric effect and the required salaries? And do higher GDP per capita regions attract more commuters, in net numbers? The sources of information were the Census of 2002 (Censo02), the National Poll of Socioeconomic Characterization of 2009 (Casen09) and the New Supplementary Income Poll of 2012 (Nesil12). The results indicate that: tourism does not have a strong influence; regions with higher GDP per capita and/or salaries have more commuters in net ammounts; and the "word-of-mouth" effect can be determined.
Keywords: C67; J61; R15; 330; regional development; commutation structure; commutation impact